CORRECTION OF ASTHENIC SYNDROME IN CHILDREN WITH INFECTIOUS MONONUCLEOSIS USING CETRULIN MALATE - Kyrytsia , N.S. (The Ukrainian Scientific Medical Youth Journal, 2017)
Asthenic syndrome is a nonspecific pathological condition characterized by weakness, increased fatigue, lethargy, which occurs not only after the load, but also without it, and do not disappear after rest. Epstein-Barr virus is a trigger factor in the development of asthenic syndrome. Now it can be argued that a viral infection is a kind of biological stressor that affects nitrogen metabolism through metabolic disorders of cortisol. As a result of hypoxia, which leads to the switching of the aerobic pathway of glycolysis to anaerobic and acidosis at the cellular level, there is an energy starvation of the whole organism. The emergence of AS is associated with the depletion of the functional capabilities of higher nervous activity in the event of overexertion, as well as due to autointoxication or exogenous toxicosis, disorders in blood supply to the brain and metabolic processes in the brain tissue, allows us to consider it in a number of cases as an adaptive reaction that manifests itself in a decrease in the intensity of activity of various systems organism with the subsequent possibility of restoration of their functions. 67 children with infectious mononucleosis, who had clinical and laboratory signs of asthenic syndrome (cognitive, emotionally labile, vegetative, somatic disorders, urine tests by express method with semiquantitative determination of ketone bodies concentration and pH revealed the presence of secondary acetone syndrome in most of the subjects, disorders of cerebral hemodynamics, deviations from the EEG norm). Correction with citrulline malate (2 g of the drug twice a day). After taking the drug for a month, the psychological state of patients improved, anxiety worsened, memory improved, and improvement in cerebral vascular dopplerography was noted. Based on the results of the study, it can be concluded that the treatment of asthenic syndrome in children with infectious mononucleosis with citrulline malate has a positive result.